The cecropin-prophenoloxidase regulatory mechanism is a cross-species physiological function in mosquitoes - Liu, Wei-Ting; Chen, Cheng-Chen; Ji, Dar-Der; Tu, Wu-Chun (iScience, 2022)
This study's aim was to investigate whether the cecropin-prophenoloxidase regulatory mechanism is a cross-species physiological function among mosquitoes. BLAST and phylogenetic analysis revealed that three mosquito cecropin Bs, namely Aedes albopictus cecropin B (Aalcec B), Armigeres subalbatus cecropin B2 (Ascec B2), and Culex quinquefasciatus cecropin B1 (Cqcec B1), play crucial roles in cuticle formation during pupal development via the regulation of prophenoloxidase 3 (PPO 3). The effects of cecropin B knockdown were rescued in a cross-species manner by injecting synthetic cecropin B peptide into pupae. Further investigations showed that these three cecropin B peptides bind to TTGG(A/C)A motifs within each of the PPO 3 DNA fragments obtained from these three mosquitoes. These results suggest that Aalcec B, Ascec B2, and Cqcec B1 each play an important role as a transcription factor in cuticle formation and that similar cecropin-prophenoloxidase regulatory mechanisms exist in multiple mosquito species. [Display omitted] •Cecropin B is able to regulate PPO 3 expression in the pupae•Cecropin B binds to TTGG(A/C)A motifs within the PPO 3 DNA•The knockdown of cecropin B was rescued by sequence-similar cecropin B peptides•The cecropin B-prophenoloxidase 3 regulatory mechanism is conserved in mosquitoes Biological sciences; Developmental biology; Molecular biology